E-Money : Prudential Supervision, Oversight, and User Protection - Dobler, Marc (Departmental Papers; Departmental Paper, 2021)
This departmental paper discusses the evolving prudential frameworks for nonbank issuers of electronic money. Some jurisdictions take a relatively light-touch approach to regulating electronic money issuers (EMIs). Others have sought to apply more stringent requirements to protect electronic money (e-money) users, as the sector has grown in importance. The paper aims to build on previous IMF staff contributions to the literature and to draw policy conclusions for strengthening e-money regulatory regimes; in particular in jurisdictions where issuers, individually or collectively, have grown to a size to which they are of macro-financial importance (see below). Chapter 2 provides background on the development of e-money, its economic benefits, and potential risks. Chapter 3 discusses prudential supervision of EMIs, followed in Chapter 4 by their oversight from a payments system perspective. Chapter 5 discusses potential additional measures for user protection and contingency arrangements for EMI failure. The last chapter presents policy recommendations for policymakers, especially in those emerging market economies and developing countries wherein EMIs have reached a scale at which they could have a significant economic impact if they were to fail.